Extracorporeal membrane oxygenation in critical airway interventional therapy: A review - Wu, Hongxia; Zhuo, Kaiquan; Cheng, Deyun (Frontiers in Oncology, 2023)
Introduction Extracorporeal membrane oxygenation (ECMO) is widely used during refractory cardiac or respiratory failure, and some case reports described ECMO utilization in critical airway interventional therapy. Methods Eligible reports about patients receiving airway interventional therapy under ECMO were retrieved from Web of Science, Embase, Medline, and Cochrane databases up to 1 August 2022. Results Forty-eight publications including 107 patients who underwent ECMO for critical airway problems met the inclusion criteria. The critical airway problem that was reported the most was tumor-associated airway obstruction (n = 66, 61.7%). The second most reported etiology was postoperative airway collapse or stenosis (n = 19, 17.8%). The main interventional therapies applied were airway stent placement or removal (n = 61, 57.0%), mass removal (n = 22, 20.6%), and endotracheal intubation (n = 12, 11.2%) by bronchoscopy. The median ECMO duration was 39.5 hours. Eleven patients had ECMO-associated complications, including seven cases of airway hemorrhage, one case of arteriovenous fistula, one case of vein rupture and hematoma, one case of foot ischemia, and one case of neuropraxia of the cannulation site. In total, 91.6% of the patients survived and were discharged from the hospital. Conclusion ECMO appears to be a viable form of life support for patients undergoing interventional therapy for critical airway problems.